Fibre Interplay in the Pregnant Uterus of the Frugivorous Bat Eidolon Helvum - Odukoya, Samson Oludare Ayodeji; Odukoya, Opeyemi Abimbola; Adelodun, Stephen Taiye (Journal of Morphological Sciences, 2018)
Introduction There is currently a lack of adequate information on the mating, reproduction and the reproductive anatomy of the frugivorous bat Eidolon helvum. We, therefore, investigated their uterus during the non-pregnant and pregnant states for adequate information and comparison between the two states to ascertain what histological adaptations occur during pregnancy in relation to collagen and elastic fibers.Materials and Methods A total of 47 female bats (E. helvum) were used, out of which 24 were pregnant and 23 were not. They were harvested on the Obafemi Awolowo University Campus. The animals were carefully screened, assumed to be presumably healthy and then sacrificed by cervical dislocation. The left and right uterine limbs with the uterine body and part of the placenta were fixed in 10% formal saline, processed for paraffin embedding and sectioned at 5 μm with a rotary microtome. The sections were stained using Verhoeff-van Gieson stain to demonstrate collagen and elastic fibers.Results The results showed that both uterine limbs were histologically active during pregnancy. The prevalent fiber was the elastic type during the non-pregnant state, and collagen type during pregnancy.Conclusion We conclude that elastic fibers tend to obey Hooke's law during pregnancy in the uterus of the frugivorous bat E. helvum, which signifies a form of histomorphological response or adaptation to pregnancy in the uterus of this bat species.
Keywords: eidolon helvum; uterus; fiber; gravid; non-gravid